Impact of BIM on Government Policy and Regulation in Infrastructure - Gentjana REXHAJ (Communications of International Proceedings, 2024)
Building Information Modelling (BIM) has established itself as a transformative technology in the construction and infrastructure industry. This study examines the impact of BIM on government policy and regulation in infrastructure. BIM enables the creation of digital models that contain comprehensive information on materials, costs and schedules, allowing for more efficient planning, construction and operation of infrastructure projects. Governments around the world are recognising the benefits of BIM and are adapting their policies and regulations accordingly to improve the efficiency, sustainability and quality of construction projects. One of the main challenges is the development of new standards and the adaptation of existing regulations, which requires close collaboration between different stakeholders. In addition, BIM offers the possibility to manage data over the entire life cycle of a building, leading to more informed decision-making processes. This study shows that the integration of BIM into government policy brings positive change and progress, particularly by promoting sustainable practices and improving the transparency and efficiency of construction projects. It becomes clear that BIM can play an important role in modernising government policy and regulation and creating long-term benefits for society.
Keywords: Building Information Modelling (BIM); government policy; regulation; infrastructure; sustainability; efficiency